Mitigating Delay in Public Projects Delivery in Malaysia - Md Yusof, Aminah; Abidin, Izieadiana; Ali Raza Khoso; Chai Chang Saar (2021)
This book presents the theoretical and empirical findings for the delay in public construction projects in Malaysia. The work starts with a critical review of the delay which is caused by contractor-related, client-related, and consultant-related factors. As public projects are a matter of interest in this research, a discussion concerning the government’s commitment in public projects and public projects’ performance is presented in this book. Based on the analysis of the selected 79 public projects, the research concludes that incompetent project team members in relation to technical, management, financial, time management, procedural knowledge, teamwork, and ethical practise. As a result, the implementation of public projects face numerous serious problems which has led to the delay and abandonment of such projects. The research concludes that the delay mitigation strategy should start with the formation of competent team members. The selection of team members should strictly follow the guidelines prepared by the government. The clients ought to possess the knowledge and necessary skills to manage the project. The need to promote effective team work and to reap the benefits of synergy is further suggested by the idea of having an ice-breaking and brainstorming session for team members. A competent, effective, and efficient team will ensure the successful delivery of public projects in Malaysia. Amid the pandemic affecting 2020, this research book also addresses the delays contributed by Covid-19. The chapter, however, is limited as it only provides situations based on observations and materials made available during the lockdown owing to the pandemic.